An assessment of the impact of the development and use of the NCC-developed government website template and the website content management systems - Amberong, Grace Martha T. (Quezon City University of the Philippines Diliman, 2005)
Realizing the impossibility of all agencies to comply with the mandate of the e-Commerce Act (Republic Act 8792 of June 2000) President Arroyo gave a new directive in a meeting at the then Information Technology and E-Commerce Council (ITECC) in April 2002. The National Computer Center (NCC), being the lead IT agency in the government was tasked to coordinate with various government departments to comply with at least Stage One-Emerging Web Presence of the United Nation-American Society for Public Administration (UN-ASPA) Five Stages of e-Government. Acting on this directive, the NCC initiated the Government Website Development Project. The NCC Project involved the development of a technology solution, which is the first version of the Government Website Template together with the Website Content Management System (WCMS) and the subsequent diffusion of this solution to all government agencies. The development of the WCMS and the Website Template addressed the concern of agencies specially those that do not have the infrastructure and technical expertise to comply with the directive of the President to have at least an emerging web presence. Representatives from various government agencies underwent website development/workshops. Technical assistance was also extended to agencies to ensure the proper use and implementation of the said technology solution. After a year of extending technical assistance, the NCC reported in May 2003 that there are 98.4 percent (%) National Government Agencies (NGAs) accessible to the Internet. The data for Local Government Units (LGUs) is even more encouraging, 98.45 percent provinces and cities and 64.6 percent municipalities are now available in the Internet. Likewise, 96 percent State Universities and Colleges (SUCs) are now online. This development prompted the NCC to develop the second version of the Website Template and WCMS to facilitate government agencies to progress to Stage 2 (Emerging Web Presence) and Stage 3 (Interactive Web Presence) of the UN-ASPA Five Stages of e-Government. Consequently, the next series of "handholding" workshops free of charge were also conducted with the participation of 121 NGAs, 212 LGUs and 53 SUCs. This TM project paper defines the statement of the problem, highlights the significance, defines the methodology and describes the results and recommendations on NCC's intervention in increasing the emergence of government agencies' web presence. Apparently, based on the statistical figures presented in NCC's website monitoring activity, it can be surmised that the completed Website Development Project was able to achieve its objective of putting the government agencies on the web. However, there has been no evaluation done on the merits and impacts of the NCC project. The primary objective of this TM project is to determine the merits and impact of NCC's Government Website Development Project with the technology solution developed and diffused to various government agencies. Likewise, this TM project also aims to assess the aptness of the technology used and to recommend possible innovation of the developed technology solution. The methodology for this TM project will consist of a combination of a conduct of a survey, literature research (library and Internet) and personal interviews. This TM project commenced in November 2004 and completed in February 2005. Based on the result of the assessment of the NCC Project and discussions on technology diffusion concepts and principles the following recommendations are being made before the NCC engage in a similar project. At the planning stage, strategies for the Five Stages of Adoption. There is a need for the NCC to include in its future project internal capability development. Training must be combined with learning by doing and using, i.e. being able to repeat tasks and research and experiment to resolve problems. Identify beneficial new technologies and diffused in an orderly manner. Engage in collaborative research and technology projects to address the gaps between technology development and deployment. Formulation of standards to facilitate the diffusion of quality measurement techniques and the avoidance of duplicative tasks.
In partial fulfillment of the requirements for the Technology Management Program
Thesis
Keywords: Technological innovations; Government website template; Website content management systems